Variation in the skulls of Elgaria and Gerrhonotus (Anguidae, Gerrhonotinae) and implications for phylogenetics and fossil identification - Ledesma, David T.; Scarpetta, Simon G.; Bell, Christopher J. (PeerJ, 2021)
Background There are limited data on intra- and interspecific osteological variation for many squamate clades. Those data are relevant for phylogenetic analyses that use osteological characters and for apomorphic identifications of fossils. We investigate whether morphological features in the skulls of extant gerrhonotine lizards can be used to distinguish taxa at the species- and genus-level and assess whether newly discovered intra- and interspecific osteological variation alters the utility of previously reported apomorphic features. We examined skulls of species belonging to the gerrhonotine genera Elgaria and Gerrhonotus. These genera contain 17 extant species, but the cranial osteology of only a few species was previously examined. As a result, intra- and interspecific osteological variation of these gerrhonotines is poorly understood. Methods We employed high-resolution x-ray computed tomography (CT) to scan 25 alcohol-preserved specimens. We provide data on the skulls of all eight species of Elgaria, four for the first time, and five species of Gerrhonotus, three for the first time. We examined 3-D reconstructed skulls of the scanned specimens as well as dry, traditionally prepared skeletons (when they were available). Results We found that the purported diagnostic utility of many previously described morphological features is impacted because of substantial morphological variation between and within species. We present an assessment of osteological differences that may be useful to differentiate species of Elgaria and Gerrhonotus, many of which are present on isolated cranial elements commonly recovered as fossils, including the premaxilla, maxilla, parietal, pterygoid, prootic, dentary, and surangular. We demonstrate the importance of documenting patterns of osteological variation using large sample sizes, and the utility of examining disarticulated cranial elements of the squamate skull to identify diagnostic morphology. This study adds to a growing body of literature suggesting that extensive documentation of morphological variation is needed to further our understanding of the phylogenetic and diagnostic utility of morphological features across vertebrate clades. Efforts in that direction likely will benefit from examination of disarticulated skeletal elements.
Keywords: Skull; Variation; Lizard; Elgaria; Gerrhonotus; Osteology; Fossils; CT